MENILAI MENILAI EFEKTIVITAS DIGITAL MARKETING CV.HAYAT HANDAYANI DENGAN PENDEKATAN AIDA - Khairudin, Khairudin; caniago, Ulung (Jurnal Bisnis Darmajaya, 2025)
In the era of globalization and digital transformation, many businesses face challenges in maximizing the potential of digital marketing, including CV. Hayat Handayani, which previously experienced limited market reach and stagnant customer interactions. This situation prompted the need to evaluate the effectiveness of the company's digital marketing implementation. This study aims to assess the extent to which digital marketing strategies can support improved business performance. The research method used a qualitative approach through in-depth interviews with three informants. The results showed that digital marketing provided significant improvements in several indicators, such as sales growth in the first three months, expanding audience reach outside the region, and increasing social media interactions. Analysis based on the AIDA model showed that the Awareness and Interest stages were the most dominant aspects, driven by the use of visual content, paid advertising, and collaboration with local influencers. Meanwhile, the Action stage still requires strengthening the consistency of purchase calls and optimizing transaction features. This study concluded that digital marketing implementation has been effective, but still requires strategic improvements to achieve more optimal results. These findings are expected to serve as a reference for companies in developing more targeted digital marketing strategies.. Keywords —Effectiveness, Implementation, Digital Marketing